Nano-Based Drug Delivery Systems of Potent MmpL3 Inhibitors for Tuberculosis Treatment - Patrizia Nadia Hanieh; Sara Consalvi; Jacopo Forte; Gianluigi Cabiddu; Alessandro De Logu; Giovanna Poce; Federica Rinaldi; Mariangela Biava; Maria Carafa; Carlotta Marianecci (Pharmaceutics, 2022)
Tuberculosis remains one of the world’s deadliest infectious diseases, accounting for nearly 1.3 million deaths every year. Tuberculosis treatment is challenging because of the toxicity, decreased bioavailability at the target site of the conventional drugs and, most importantly, low adherence of patients; this leads to drug resistance. Here, we describe the development of suitable nanocarriers with specific physicochemical properties to efficiently deliver two potent antimycobacterial compounds. We prepared nanoemulsions and niosomes formulations and loaded them with two different MmpL3 inhibitors previously identified (NEs + BM635 and NIs + BM859). NEs + BM635 and NIs + BM859 were deeply characterized for their physicochemical properties and anti-mycobacterial activity. NEs + BM635 and NIs + BM859 showed good hydrodynamic diameter, ζ-Potential, PDI, drug-entrapment efficiency, polarity, and microviscosity and stability. Even though both formulations proved to perform well, only NIs + BM859 showed potent antimycobacterial activity against M. tuberculosis (MIC = 0.6 µM) compared to that of the free compound. This is most probably caused by the fact that BM635, being highly hydrophobic, encounters maximum hindrance in diffusion, whereas BM859, characterized by high solubility in aqueous medium (152 µM), diffuses more easily. The niosomal formulation described in this work may be a useful therapeutic tool for tuberculosis treatment, and further studies will follow to characterize the in vivo behavior of the formulation.